Different Reactivity of As4 towards Disilenes and Silylenes. Issue 23 (4th May 2017) - Seitz, Andreas E.; Eckhardt, Maria; Sen, Sakya S.; Erlebach, Andreas; Peresypkina, Eugenia V.; Roesky, Herbert W.; Sierka, Marek; Scheer, Manfred
Abstract: The activation of yellow arsenic is possible with the silylene [PhC(NtBu)2 SiN(SiMe3 )2 ] (1 ) and the disilene [(Me3 Si)2 N(η 1 ‐Me5 C5 )Si=Si(η 1 ‐Me5 C5 )N(SiMe3 )2 ] (3 ). The reaction of As4 with1 leads to the unprecedented As10 cage compound [(LSiN(SiMe3 )2 )3 As10 ] (2 ; L=PhC(NtBu)2 ) with an As7 nortricyclane core stabilized by arsasilene moieties containing silicon(II)bis(trimethylsilyl)amide substituents. In contrast, the compound [Cp*{(SiMe3 )2 N}SiAs]2 (4 ) containing a butterfly‐like diarsadisilabicyclo[1.1.0]butane unit is formed by the reaction of As4 with the disilene3 . Both compounds were characterized by single‐crystal X‐ray diffraction analysis, NMR spectroscopy, and mass spectrometry. The reaction outcomes demonstrate the different reaction behavior of yellow arsenic (As4 ) compared to white phosphorus (P4 ) in the reactions with the corresponding silylenes and disilenes. Abstract : As revealed : The reaction of yellow arsenic with the silylene [PhC(NtBu)2 SiN(SiMe3 )2 ] and the disilene [(Me3 Si)2 N(η 1 ‐Me5 C5 )Si=Si(η 1 ‐Me5 C5 )N(SiMe3 )2 ] gives an As10 cage compound with a nortricyclane core and a diarsadisila‐butterfly derivative, respectively. These reactions demonstrate the different reaction behavior of yellow arsenic As4 and white phosphorus P4 with the corresponding silicon derivatives.